Rating jakości zarządzania ryzykiem firmy - Krysiak, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the important issues of integrated corporate risk management (IRM). The main purpose of the paper was to present some idea of rating model to evaluate the quality of risk management within corporate and financial institution. The results of the research indicate that the assumed model of rating is very highly corelated with financial outcomes of companies chosen for analyzis. The results indicate a high demand for the promotion of IRM and prove that companies operating in Poland get better results when high IRМ quality is applied. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 193-206